2016
DOI: 10.1037/dev0000149
|View full text |Cite
|
Sign up to set email alerts
|

Changes in frontal EEG coherence across infancy predict cognitive abilities at age 3: The mediating role of attentional control.

Abstract: Theoretical perspectives of cognitive development have maintained that functional integration of the prefrontal cortex across infancy underlies the emergence of attentional control and higher cognitive abilities in early childhood. To investigate these proposed relations, we tested whether functional integration of prefrontal regions across the second half of the first year predicted observed cognitive performance in early childhood indirectly through observed attentional control one year prior (N=300). Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 105 publications
(155 reference statements)
1
25
1
4
Order By: Relevance
“…These atypical scanning patterns may point to a larger problem. Given that attention is a multi-faceted construct, 9 and is foundational to many areas of cognitive growth, [10][11][12][13][14] we examined three core components of this domain: Sustained attention, maintaining focus on a target while ignoring distractors; 15 Disengagement of Attention, shifting focus while ignoring competing information (submitted);…”
Section: Introductionmentioning
confidence: 99%
“…These atypical scanning patterns may point to a larger problem. Given that attention is a multi-faceted construct, 9 and is foundational to many areas of cognitive growth, [10][11][12][13][14] we examined three core components of this domain: Sustained attention, maintaining focus on a target while ignoring distractors; 15 Disengagement of Attention, shifting focus while ignoring competing information (submitted);…”
Section: Introductionmentioning
confidence: 99%
“…However, our results suggest that, before the first birthday, left lateralization is already apparent when a receptive language paradigm is performed (Asano et al, 2015). Moreover, a greater left connectivity before 5 years of age has been correlated with better language abilities (Mundy et al, 2003;Kikuchi et al, 2011;Kühn-Popp et al, 2016;Whedon et al, 2016). Thus, M/EEG research points toward an earlier implementation of left lateralization in language networks than was concluded from studies done with fMRI.…”
Section: Summary Of the Main Observationsmentioning
confidence: 45%
“…In healthy infants, few studies (n = 6) investigated the association between measures of coherence and later language abilities of preschoolers (Mundy et al, 2003;Marshall et al, 2008; Kikuchi (Yang et al, 2005). Specifically, between 5 and 10 months of age, an increase in resting-state EEG coherence in the theta-alpha band (6-9 Hz) within left frontal regions seems to be associated with higher cognitive functioning, including receptive language at 3 years of age (Whedon et al, 2016). This association, however, might not be specific to language functions because the authors reported a mediating influence of the level of attentional control at the age of 2 years.…”
Section: Results From Coherence In Healthy Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence, however, that infant neuroconnectivity is related to later EF. For example, Whedon, Perry, Calkins, and Bell () reported that increases in left frontofrontal EEG coherence from 5 to 10 months were associated with better performance on attentional control task at 2 years, as well as EF and language tasks at 3 years. The link between early neuroconnectivity and later social development is less well studied, and the patterns appear to vary with electrode pair, hemisphere, and development.…”
mentioning
confidence: 99%